FAKTOR - FAKTOR YANG MEMPENGARUHI TINGKAT KELANGSUNGAN HIDUP 5 TAHUN PASIEN DENGAN KANKER KANDUNG KEMIH DI RSUD DR. ZAINOEL ABIDIN BANDA ACEH - Merysia Karmila; Jufriady Ismy; Imam Hidayat; Safrizal Rahman; Muhammad Ridha; Muhammad Azmi Fanany (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Bladder cancer is the tenth most common cancer worldwide, and its prevalence is gradually increasing globally. In Indonesia, there are 7,828 new cases of bladder cancer each year, which cause 3,885 deaths. The survival of bladder cancer patients highly depends on many factors. Objective: To identify the factors that influence the 5-year survival rate of patients with bladder cancer at zainoel abidin hospital. Method: An analytical one year study using a retrospective cohort design to analize the factors affecting the 5-year survival rate of bladder cancer patients for 5 years, starting from 2015 until 2019 with medical record data. Result: The average age of the 151 patients was 59±11.9 years, and 126 patients (83,4%) were male. The majority 105 patients (69.54%) were under 65 years old. A total of 127 patients (84.11%) were smokers, 65 patients (43%) with high school degree, 50 patients (33,11%) were self-employed, 96 patients (63.58%) is underweight BMI. Based on stadium of bladder cancer, the majority of patients (34.44%) had T3, and the most common treatment (78.81%) was TURBT and refused to radikal cystectomy. Patient survival rates were influenced by age (P value = 0.00), education level (P value = 0.003), occupation (P value =0,01), treatment (P value = 0,005), and T category (P value = 0.00). Conclusion: Age, education level, occupation, treatment and T category have a significant impact on bladder cancer patients survival rate. Keywords: Bladder cancer, 5-years survival, Age, Education level, Occupaton, Smokers, BMI, T Category, Treatment.